IMPLEMENTASI PENDEKATAN CRT BERBANTUAN MEDIA KARTU BERGAMBAR UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA PADA PESERTA DIDIK KELAS III SD - Anggi Silfianasari; Budiyono; Hapsari Dewi; Yunita Wulandari; Roy Adi Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The lack of variety in approaches and media used in the learning process has resulted in conventional, teacher-centered learning activities, leading to low student achievement in Indonesian language learning. This study is a classroom action research aimed at improving student achievement through the implementation of the Culturally Responsive Teaching (CRT) approach assisted by picture cards. The research was conducted in two cycles, which included planning, implementation, observation, and reflection stages. The subjects of the study were 24 students from class III-B at SD Labschool Unesa 2. Data were collected from teachers and students through observations and evaluation tests. The data analysis techniques used were both quantitative and qualitative descriptive analyses. The results showed an improvement in student achievement in each cycle. Overall, the average percentage of students' learning mastery in the first cycle was 21%, which then increased to 62% and reached 83% in the second cycle. Based on data analysis, it can be concluded that the CRT approach assisted by picture card media successfully improved student achievement as it met the predetermined success criteria, with more than 80% of students achieving the minimum competency score (KKM) of ≥ 80.